The role of personality for gender gaps in political interest and activity - Adam Ayaita (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Women have been found to be, on average, less interested in politics and less politically active than men, which might reduce the representation of women's interests in a democracy. In order to enhance the understanding of these gender gaps, this preregistered study analyzes the role of personality differences for gender gaps in political interest and activity. I use a large representative sample of the adult population in Germany for the analysis. First, I replicate the findings that women tend to have lower scores in political interest and activity and that these gaps are not fully explained by demographic, situational, and structural factors. Second, I find that the remaining gender gaps in political interest and activity are, overall, not significantly explained by gender differences in personality. However, gender differences in some specific personality traits partially explain the political gender gaps: Women's higher average agreeableness contributes to the gender gap in political interest, and women's higher average conscientiousness contributes to the gender gap in political activity.
Keywords: 330; gender; personality; political activity; political engagement; political interest; politics